Možnosti rehabilitacije kognitivnih sposobnosti, relevantnih za vožnjo osebnega avtomobila, pri bolnikih po možganski kapi - Mlinarič Lešnik, Vesna (Rehabilitacija (Ljubljana), 2022)
Objective: The cognitive consequences of a stroke significantly affect a person’s ability to drive safely again. However, a person’s recovery in cognitive abilities can be aided by cognitive rehabilitation interventions. Some interventions specifically target the recovery of driving ability. These can be divided into two areas: training specific skills that are impaired and a contextual approach that trains driving-specific activities. The aim of our paper was to review the recent literature in this field. Methods: The PubMed and Ovid databases were searched using key words “driving”, “stroke”, “rehabilitation” or “training”. Results: We found a total of six articles (five research articles and a Cochran review article). In two studies, specific skills training did not contribute to patients’ performance on the practical test. Driving training with a simulator or in the form of driving lessons with an instructor has resulted in better performance on the practical test. Conclusion: We reviewed studies that examined the effectiveness of both aforementioned approaches. In most studies, training of both types resulted in better performance on the practical driving evaluation, but research is still scarce, therefore there are no clear conclusions yet about incorporating such training into rehabilitation.
Keywords: Automobile Driving; cognition; cognitive rehabilitation; driving; kognicija; kognitivna rehabilitacija; možganska kap; Stroke; vožnja